Daredevil: black armor (2024) ebook - Various, Marvel (Daredevil: Black Armor (2024), 2024)
Daredevil: Black Armor #1-4. Daredevil is back in black! Acclaimed writer D.G. Chichester returns to Hell's Kitchen for an all-new story set during his landmark 1990s run on the series! And Matt Murdock will need to push his extraordinary senses - and his stylish black-and-red armored costume - beyond their limits if he hopes to even stand a chance against what's coming. Because DD is about to be embroiled in a conflict involving the Hobgoblin, the Kingpin, Spider-Man and a mysterious foe whose powers trump them all! Who is the maestro behind the Machiavellian machinations plaguing Hell's Kitchen? Find out as the Man Without Fear, his friends and foes alike - face a battle for their lives beneath the city's busy streets!